SHELLQs. Bridging the Gap: JWST Unveils Obscured Quasars in the Most Luminous Galaxies at z > 6 - Yoshiki Matsuoka; Masafusa Onoue; Kazushi Iwasawa; Kentaro Aoki; Michael A. Strauss; John D. Silverman; Xuheng Ding; Camryn L. Phillips; Masayuki Akiyama; Junya Arita; Masatoshi Imanishi; Takuma Izumi; et al. (The Astrophysical Journal)
The unprecedented sensitivity of the James Webb Space Telescope (JWST) has uncovered a surprisingly abundant population of mildly obscured, low-luminosity active galactic nuclei (AGNs) in the epoch of reionization (EoR). However, the link between these objects and classical unobscured quasars remains a mystery. Here we report the discovery of obscured quasars hosted by the most luminous galaxies at z > 6, possibly bridging the gap between the two AGN populations. The 13 objects presented here were originally selected from a rest-frame ultraviolet (UV) imaging survey over >1000 deg ^2 , and were known to have luminous (>10 ^43 erg s ^−1 ) Ly α emission. With JWST/NIRSpec follow-up observations, we found that 7 out of 11 objects with narrow Ly α exhibit a broad component in H I Balmer lines and He I lines, but not in [O III ] and other forbidden lines. Mild dust obscuration (0 < A _V < 3) is inferred from the Balmer decrements. The estimated intrinsic luminosities suggest that our broad-line (BL) objects are the long-sought UV-obscured counterparts of luminous quasars in the EoR. They host supermassive black holes (SMBHs) with masses 10 ^7.8−9.1 M _⊙ , undergoing sub-Eddington to Eddington accretion. Most of the BL objects are spatially unresolved and are close to “little red dots” with their blue rest-UV and red rest-optical colors. We estimate the AGN number density among similarly luminous Ly α emitters to be larger than 2 × 10 ^−8 Mpc ^−3 . This density is comparable to that of classical quasars with similar continuum luminosities, suggesting that a substantial fraction of active SMBHs are obscured in the EoR and have been overlooked in past rest-UV surveys.